Ignorance of Local Needs in Construction of New Houses of the Earthquake Hit Dalit Community in Central Nepal - Acharya, Bhesraj; Sharma, Dhurba Prasad (Namuna Academic Journal, 2023)
This article asserts ignorance of local knowledge system, need, social, and cultural settings in construction of earthquake resilient houses in Dalit community. Dalit communities are considered as economically backward ethnic caste group in Nepal. The article is based on the field study carried out in Dhading district of Bagmati Province. The guiding theoretical framework of the study is the anthropology of disaster focusing on resilience through holistic approach to reveal undermining of local contexts in reconstruction of private houses. The methodological approach consists of qualitative research tools supplemented by household census.As part of earthquake resilient house construction, the government of Nepal provided cash grant support to the families with severely damaged houses. Such families identified as red card holders. Findings of the study clearly reveal that the cash support is not enough to address the local social and cultural needs of Dalits in construction of houses. There is heterogeneity in Dalit communities in terms of social cultural bonding, social relations, and economic status. The cash support in the lump sum basis under the blanket policy approach regardless of household income, family background, and economic status hardly address the local contexts. Most importantly, the construction process highly concentrated on building of house structures in the prescribed standards of the government focusing on technical engineering rather than accommodation of local settings and needs.